‘Qui Es-Tu Sous La Ressemblance | Qui Va Là Sous Couvert De Moi’: the Hourglass of Poetic Identity in Bernard Noël's ‘L'ombre Du Double’ - Andrew Rothwell (The Modern Language Review, 2015)
Much of Bernard Noël's poetry develops out of phenomenological processes of reflection and inversion, figured metapoetically by the sablier image and its avatars. Among these is the (dark) mirror, which initiates the poet's investigation of selfhood and writing in the important poem sequence ‘L'Ombre du double’ of 1993. This study explores the complex variations which Noël weaves, here and elsewhere, on the key terms ombre and double, to construct the page as a ‘maison d'envers’—a mental space where past, present, and future merge, where self and other, poet and reader interact, and where the limits of poetic language are tested.